Isolation of Bacillus Cereus from Meat Ready to Eat Using Antimicrobial Resistance Pattern and Polymerase Chain Reaction - Deoxyribonucleic Acid (DNA-PCR) - Ahlam Abdaslam M. Ali (African Journal of Advanced Pure and Applied Sciences, 2024)
In September 2022, a total of 50 samples of ready-to-eat mutton meat were purchased from 10 different restaurants in Tripoli, Libya. Twelve isolates were identified as B. cereus through biochemical analysis. These isolates exhibited positive results for lecithinase production, starch hydrolysis, nitrate reduction, catalase production, Gram stain, and glucose fermentation, Nacl. No positive results were obtained for indole, sucrose, gas production , and lactose fermentation in any of the samples, blood hydrolysis To determine the relatedness and diversity of the B. cereus strains from RTE mutton meat, polymerase chain reaction was performed using primer S16. The antimicrobial pattern Erythromycin 88 %, Chloramphenicol 81.4 %, Trimothprim 93 % Clindamycin 90.7 %, Pencillin 100 % , Amikacin 76.4 % By combining the phenotype and genotype methods, a total of nine different types of B. cereus were identified. These findings provide evidence for the existence of both relatedness and diversity among the B. cereus strains isolated from mutton meat.